Hungarian Monitoring, 9 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American intervention in the Middle Eastern crisis - American soldiers in Saudi Arabia - Arab summit in Cairo - Compromise between Armenian president and Moscow - Government crisis in Prague - Corruption scandal in Poland - Kohl obstructs Honecker's trip to Chile - Japan remembers the Nagasaki catastrophe Domestic Affairs: - Debate about reprivatization - Géza Jeszenszky at talks in Vienna proposes armed forces framework - Visa waiver between Hungary and Iceland - Electoral districts outlined - László Tőkés undergoes three-hour operation - Landslide in Visonta Economy: - Hungarian compensation demand for cancelled East German shipments - Food prices have risen 33% in one year Külpolitika: - Amerikai beavatkozás a közel-keleti válságban - Amerikai katonák Szaúd-Arábiában - Arab csúcs Kairóban - Kompromisszum az örmény elnök és Moszkva között - Kormányválság Prágában - Korrupciós botrány Lengyelországban - Kohl megakadályozza Honecker chilei útját - Japán a nagasaki katasztrófára emlékezik Belpolitika: - Vita a reprivatizációról - Jeszenszky Géza a bécsi tárgyaláson javasolt haderőkeretről - Megszűnő vízumkényszer Magyarország és Izland között - Megkezdődik a szavazókörök kialakítása az országban - Tőkés László háromórás műtéten esett át - Földcsuszamlás Visontán Gazdaság: - Magyar kártérítési igény az elmaradt keletnémet szállítások miatt - Egy év alatt 33%-kal emelkedtek az élelmiszerárak